The Adequacy of the Theory of Logical Function Applied to Some Clauses in Chinua Achebe’s Novel Things Fall Apart - Mardianto, L; Suhadi, J; ., Purwarno (KnE Social Sciences, 2018)
This paper is concerned with the evaluation of the theory of Logical Function introduced by Halliday (1994, 2014) under the theoretical framework of Systemic Functional Grammar. The goal of this research is to examine whether the theory is adequateto be applied to analyze clause complexes in the novel Things Fall Apart written by Chinua Achebe. The study applied qualitative method as proposed by Sugiono (2017). The analysis focuses on the description of clause complexes used in the novel from both Interdependency Relation and Logico-semantic Relation. The finding shows that the theory of logical function is adequate to be applied to analyze clause complexes in the novel under research. The evidence is based on the fact that all types of clause complexes as postulated in the theory of logical function are found in the novel, as the sample of natural language. The types of clause complexes used in the novel cover paratactic elaboration, hypotactic elaboration, paratactic extension, hypotactic extension, paratactic enhancement, hypotactic enhancement, paratactic locution, hypotactic locution, paratactic idea, and hypotactic idea. Keywords: logical function, interdependency relation, logico-semantic relation.